CONCATENATIONS: On the Works of Olga Tokarczuk. - CZAPLIŃSKI, PRZEMYSŁAW (Polish Review, 2021)
This paper is a micro-synthesis of Olga Tokarczuk's prose works. The initial assumption is that the main driving force in the author's prose narratives is desire which determines the actions of her protagonists and influences the genre of said works. This assumption allows for discovery of discrete stages in Tokarczuk's prose fiction. In the first stage from Podróż ludzi Księgi [The journey of the people of the book, 1993] to Prawiek i inne czasy [Primeval and other times, 1996], the strongest driving force is the desire for knowledge. In the second period from Dom dzienny, dom nocny [House of day, house of night,1998] to Bieguni [Flights, 2007] the desire is to focus on the Other, taking the form of solidarity. Finally, in the third period from the novel Prowadź twój pług przez kości umarłych [Drive your plow over the bones of the dead, 2009] to Księgi Jakubowe [The books of Jacob, 2014], the desire is directed against unjust laws, presupposing a recognition of the world order, and defining obligations towards other lives.